Effect of sodium alginate concentration on characteristic, viability, and antibacterial activity of probiotic-alginate microparticles - Dewi, Melani Hariyadi (Atom and Cell Publisher, 2015)
Probiotic (Lactobacillus acidophilus) has been known as an effective antibacterial activity, however storage, high oxygen levels, and gastric acid condition was generally decrease the probiotic viability. To maintain the probiotics’ viability, extrusion technique was selected to produce microparticles. This technique used sodium alginate polymer and calcium chloride cross linking solution. This research investigated effect of sodium alginate concentration on the physical characteristics, viability and antibacterial activity. Results showed that increasing alginate concentration from 2.5% to 3.5% increased microparticle size (from 15.40µm to 37.53µm). Viability of Lactobacillus acidophillus of all formulas were above 94%, however an increased of alginate concentration did not significantly affect antibacterial activity. The extrusion method demonstrated its potential in encapsulation of Lactobacillus acidophillus for probiotics delivery.